Placing Camelot: Cultivating leadership and learning in the Kennedy presidency. (February 2022) - McCann, Leo; Mollan, Simon
The concept of 'place' can play a powerful role in understanding how leadership is socially constructed. This article explores the geographic, symbolic and mythic uses of place in the cultivation of a distinct leadership style around the Presidency of John F. Kennedy. It focuses on the history of a social and learning event that today might be called a leadership development programme: the 'Hickory Hill Seminars' of 1961-4, named after and mostly held at the specific location of Robert F. Kennedy's home. These seminars – only lightly touched on in Kennedy-era history and leadership literatures – were semi-formal occasions organized by the historian Arthur Schlesinger that brought eminent public intellectuals of the day to present their work to the assembled group of insiders. The seminars functioned as a network in action, both cultivating and projecting certain cultural formations of leadership. Bounded by the geographic places inhabited by Washington elites, the seminars formed part of the broader construction of the symbolic place of the 'New Frontier' and the mythic place of 'Camelot'. The Hickory Hill seminars were one part of a broad metaphysical canvas upon which a distinct presidential leadership style and 'legacy' was created. Building on critical and social constructivist perspectives, we argue that geographic, symbolic and mythic notions of place can be central to the social construction of particular leadership styles and legacies, but that these creations can be deceptive, and remain always vulnerable to critique, co-optation and distortion by opponents and rivals.